Factors affecting K-economy readiness: a study in higher education - Umi Nuraini; Sheerad Sahid; Muhammad Hussin (Instituto Politécnico de Viseu, 2024)
Introduction: Higher education plays a crucial role in the innovation system of the K-economy by generating substantial scientific and technical advancements and fostering innovative individuals. It is essential to investigate the K-economy readiness of the education sector, as past studies have mostly focused on this topic in the industrial sector. Objective: To determine the effect of entrepreneurial thinking, ICT skills, social and cross-cultural skills, and career readiness on the K-economy readiness of undergraduate students. Methods: This research question was answered using multiple regression analysis of survey data collected from 578 undergraduate students of Economics Education at six teacher-based universities on the island of Java, Indonesia. Results: This study found that entrepreneurial thinking, ICT skills, social and cross-cultural skills, and career readiness all positively and significantly affect the K-economy readiness of undergraduate students. Conclusion: Implementing education policy adjustments based on this study's findings can enhance student knowledge and skill development in higher education to increase competitiveness in the K-economy. Higher education needs to rely on information and innovation to effectively contribute to economic and social growth sustainably through the K-economy.